Prevalence and Clinical Significance of Discordant Changes in Fractional and Coronary Flow Reserve After Elective Percutaneous Coronary Intervention - Junji Matsuda; Tadashi Murai; Yoshihisa Kanaji; Eisuke Usui; Makoto Araki; Takayuki Niida; Sadamitsu Ichijyo; Rikuta Hamaya; Tetsumin Lee; Taishi Yonetsu; Mitsuaki Isobe; Tsunekazu Kakuta (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
Background Fractional flow reserve (FFR) and coronary flow reserve (CFR) are well‐validated physiological indices; however, changes in FFR and CFR after percutaneous coronary intervention (PCI) remain elusive. We sought to evaluate these changes and to investigate whether physiological indices predict cardiac event‐free survival after PCI. Methods and Results Physiological assessment of 220 stenoses from 220 patients was performed before and after PCI. The changes in FFR and CFR were studied, and factors associated with CFR change were investigated. Follow‐up data were collected to determine the predictor of cardiac events. CFR increase was found in 158 (71.8%) territories, and 62 (28.2%) presented a decrease, whereas FFR increased in all 220 (100%) territories. Pre‐ and post‐PCI percentage diameter stenoses were 57.7±11.2% and 7.48±4.79%, respectively. Post‐PCI CFR increase was associated with pre‐PCI indices including low FFR, low CFR and high microvascular resistance, and post‐PCI hyperemic coronary flow increase. Post‐PCI CFR decrease was not associated with significant post‐PCI hyperemic coronary flow increase. At a median follow‐up of 24.3 months, adverse event–free survival was significantly worse in patients with lower pre‐PCI CFR (log‐rank test λ2=7.26; P=0.007). Cox proportional hazards analysis showed that lower pre‐PCI CFR (hazard ratio 0.73; 95% CI 0.55–0.97; P=0.028) was an independent predictor of adverse cardiovascular events after PCI. Conclusions CFR decrease after PCI was not uncommon, and discordant change in FFR and CFR was associated with high pre‐PCI CFR, low pre‐PCI microvascular resistance, and no significant post‐PCI hyperemic coronary flow increase. Pre‐PCI CFR, not post‐PCI physiological indices, may help identify patients who require adjunctive management strategy after successful PCI.